(untitled) (Research, Society and Development, 2020)
To evaluate in vitro the physicochemical properties of industrialized and fruit-based juices and investigate their erosive and cariogenic potentials. The sample consisted of 12 juices of different flavors (pineapple and guava) and forms of presentation: in natura, solid preparations for refreshment and produced from fruit pulp. The control group consisted of distilled water. The physicalchemical characteristics were evaluated by two trained researchers, comparing their values of hydrogen potential (pH) and total soluble solids (TSS) content. The data were analyzed and presented using descriptive statistics. The lowest pH averages observed, for each type of juice, were 2.85 ± 0.73, 3.11 ± 0.13 and 2.79 ± 0.04, these values being for in natura guava juice, for solid preparation for refreshment guava Mid® and for fruit pulp guava juice Ideal®, respectively. The highest averages of ºBrix found, according to each type of juice, were 7.00 ± 0.25, 2.65 ± 0.41 and 5.58 ± 0.14, being for in natura pineapple juice, for solid preparation for refreshment pineapple Maratá® and for fruit pulp pineapple juice Canaã®, respectively. All fruit juices evaluated showed high erosive potential, as they showed low pH, while in natura pineapple juice had the highest TSS content.